2004
DOI: 10.1080/10407780490520841
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical Study of Nonisothermal Reactive Flow in a Dual-Scale Porous Medium Under Partial Saturation

Abstract: This numerical study investigates the temperature and cure distribution during the flow of a reactive liquid in dual-scale fibrous porous media under partial saturation. An iterative, control-voiume approach, ha.sed on energy and cure balances, is usedfnr developing discretized equation.'i in the cbannels and fiber tows of the two-layer model of a dual-scale ptirttus medium. Significant differences in the average temperatures and cares within the channels and fiber tows are observed. The ratio of tbe channel a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…In the case of reactive RTM, chemical reactions occur during filling, generating evolutions in the degree of cure of the resin, coupled with heat generations and modifications of the viscosity. Pillai proposes in Pillai and Jadhav 17 a 2D model to simulate the filling of a single fiber tow, using finite elements to determine the non-isothermal flow of a reactive resin in the channel as well as in the tow. The transfer of the quantities of interest is conducted for each element, using mass, energy, or degree of cure balance.…”
Section: Previous Workmentioning
confidence: 99%
“…In the case of reactive RTM, chemical reactions occur during filling, generating evolutions in the degree of cure of the resin, coupled with heat generations and modifications of the viscosity. Pillai proposes in Pillai and Jadhav 17 a 2D model to simulate the filling of a single fiber tow, using finite elements to determine the non-isothermal flow of a reactive resin in the channel as well as in the tow. The transfer of the quantities of interest is conducted for each element, using mass, energy, or degree of cure balance.…”
Section: Previous Workmentioning
confidence: 99%
“…(Recently, Rajendra et al [38] showed, using a simple two-layer model for the dual-scale porous medium, that temperatures inside the tows can be higher by as much as 15 C when a relatively cold liquid is injected into a hot mold. Later, it was also shown [39,40] that the resin cures inside tows in such a medium is much higher than the cures in the surrounding inter-tow region.) Unfortunately, the researchers using the K unsat approach still persist with the conventional single-scale equations for temperature and cure for mold-filling simulations in LCM.…”
Section: Unsaturated Permeabilitymentioning
confidence: 98%
“…under the action of a given pressure difference. The flow of the medium in the fabric can be considered as the flow of a Newtonian fluid in a porous medium and follows Darcy's law [27] :…”
Section: Glass Fiber Fabricmentioning
confidence: 99%